Service Quality and Its Impact on Customer Satisfaction and Loyalty in Airline Industry: Partial Least Square (PLS)-Structural Equation Modelling (SEM) Approach. - ALI, JAVED; JUSOH, AHMAD; QASIM, ABUL; ABRO, MUHAMMAD AZEEM (The journal of contemporary issues in business and government, 2021)
This quantitative paper aims to measure the service quality of airline service perceived by Pakistani customers, and its impact on customer satisfaction and loyalty. Partial Least Square Structural - Equation Modelling (PLS-SEM) was used to measure the relationship. It used a self-administered questionnaire by incorporating AIRQUAL measurement model. Respondents (n=168) who have travelled from Pakistan to Malaysia were sent questionnaire through social media. Convenience sampling technique was used, and the results revealed that Airline Tangibles, Personnel Services, and Image have a positive and significant relationship with Customer Satisfaction whereas Empathy and Terminal Tangibles showed an insignificant relationship with Customer Satisfaction. Results also showed a strong positive relationship between Customer Satisfaction and Customer Loyalty. Moreover, the management of airlines and airport services need to reconsider the services they provide to their customers who are travelling from Pakistan to Malaysia.